2018
DOI: 10.1111/aas.13220
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and prediction of higher estimated gastric content in parturients at full cervical dilatation: A prospective cohort study

Abstract: Around a quarter of parturients with epidural analgesia and free access to clear fluids during labour presented higher estimated gastric content at full cervical dilatation. The SR-CSA may be of interest for the fast ultrasound assessment of the gastric content status in case of emergent obstetrical procedures at full cervical dilatation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 44 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…Epidural analgesia may affect gastric emptying of a meal in two opposite ways: on the one hand, it minimizes the acute pain related to gastroparesis via pain relief, and on the other hand, it reduces gastric motility and delays gastric emptying due to the epidural opioid infusion. 7,8,10 In our study, pain scores were significantly higher in the Parturient-No-Epidural group than they were in the Parturient-Epidural group at each time point. Taken together, the results of the current study suggest that patient-controlled epidural analgesia with a low concentration of ropivacaine and sufentanil significantly improves gastric motility and emptying compared to that seen in natural labor without analgesia.…”
Section: Discussionmentioning
confidence: 41%
See 2 more Smart Citations
“…Epidural analgesia may affect gastric emptying of a meal in two opposite ways: on the one hand, it minimizes the acute pain related to gastroparesis via pain relief, and on the other hand, it reduces gastric motility and delays gastric emptying due to the epidural opioid infusion. 7,8,10 In our study, pain scores were significantly higher in the Parturient-No-Epidural group than they were in the Parturient-Epidural group at each time point. Taken together, the results of the current study suggest that patient-controlled epidural analgesia with a low concentration of ropivacaine and sufentanil significantly improves gastric motility and emptying compared to that seen in natural labor without analgesia.…”
Section: Discussionmentioning
confidence: 41%
“…32,33 It was previously shown that solid food remained in the stomach for many hours after the onset of labor in two thirds of laboring women who received epidural analgesia and that gastric volume was higher in the immediate postpartum period in women who were allowed solid food during labor compared with those who were fasted. 11,34 More recent studies suggest that some gastric motility and emptying persist in laboring women receiving epidural analgesia 9,10 ; however, trials have appropriately assessed neither gastric emptying of a standardized, solid, light meal in parturients nor the effect of epidural analgesia during labor on the gastric emptying of such a meal. Barboni et al 35 recently reported that gastric emptying of a standardized 450-kcal solid meal composed of pasta and meat was delayed in term pregnant women scheduled for cesarean delivery compared with nonpregnant volunteers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the definition of a full stomach that increases aspiration risk is somewhat controversial, recent literatures recommend that a full stomach may be defined as any solid or thick particulate content or grade 2, or grade 1 with gastric volume of ≥1.5 ml· kg − 1 under ultrasound examination [ 7 , 10 , 21 ]. Based on this criterion, the incidence (80%) of risk stomach in non-fasted laboring women in this study was significantly higher than the laboring women allowed to drink only in other studies (27 and 48%, respectively) [ 18 , 19 ]. Moreover, the fasting time for solids, but not for liquids, was significantly associated with the antral CSA, suggesting that solid foods have a major contribution of risk stomach during labor.…”
Section: Discussionmentioning
confidence: 53%
“…As in non-pregnant adults, several studies reported a significant relationship between the semiquantitative grading scale and GFV in term pregnant women, with a significant increase in GFV along with this semiquantitative grade. 3,5 However, there are insufficient published data to support the use of this tool in the obstetrical population. Therefore, we performed a secondary analysis of data from three previously published studies to assess the diagnostic performance of the semi-quantitative ultrasound grading system for prediction of GFV in pregnant women at the third trimester.…”
mentioning
confidence: 99%